Member-sponsored projects: a case study in a graduate operations management course. (2018) - Jin, Alan; Wu, Lifang; Cunningham, Margaret; Lee, Mina
Client-sponsored projects are recognised as a powerful experiential learning tool in business education. However, instructors tend to avoid them due to a number of major obstacles. In order to overcome the shortcomings of traditional client-sponsored projects, we introduce a different type of client-sponsored project: member-sponsored group operations projects using a group member as the client. This article describes the structure of this project and how it was implemented in an MBA operations management core course and explains its distinctive features and strengths in comparison to traditional client-sponsored projects, from the instructors' perspective. The projects completed by the students, as well as the post-project face-to-face interviews with students, revealed that this pedagogical tool captures the nuances of immersion into an actual business environment. The projects enhanced students' learning and have major advantages, compared with traditional client-sponsored projects. This article concludes with the limitations of the study, implications for instructors and suggestions for future research.